1941-1945-jıllarda Qaraqalpaqstanda kitapxanalar isiniń jaǵdayı (SCIENCE and SOCIETY, 2025)
The article is dedicated to the history of the formation and development of librarianship in Karakalpakstan during the Great Patriotic War. It highlights the role of decisions made by Soviet party organs, which sought to turn libraries into strongholds of ideological work. The state of librarianship in Karakalpakstan during the war is also depicted.